Biomacromolecular interactions and radical scavenging activities of one-dimensional (1D) copper(II) glycinate coordination polymer - Inci, Duygu; Aydin, Rahmiye; Zorlu, Yunus (Springer, 2021)
One-dimensional (1D) copper(II) glycinate coordination polymer {[Cu(gly)(2)(H2O)](n); (gly: glycine)} has been synthesized and characterized by CHN analysis, ESI-MS, FTIR and single-crystal X-ray diffraction techniques. Interaction of the complex with biomacromolecules {calf thymus DNA (CT-DNA) and bovine serum albumin (BSA)} has been investigated by electronic absorption and fluorescence spectroscopy methods. The experimental outcomes indicate that the complex binds to CT-DNA by means of a moderate intercalation mode. Furthermore, the fluorescence quenching mechanism between the complex and BSA is a static quenching process. The Stern-Volmer constants, binding constants, binding sites and the corresponding thermodynamic parameters (Delta G, Delta H, Delta S) of BSA + the complex systems were determined at different temperatures. The binding distance between the complex and BSA was calculated according to Forster non-radiation energy transfer theory (FRET). The effect of the complex on the conformation of BSA was also examined using synchronous, two-dimensional (2D) and three-dimensional (3D) fluorescence spectroscopy. Radical scavenging activity of the complex was determined in terms of IC50, using the DPPH and H2O2 method. In biomacromolecules interactions and radical activity studies, the complex was found to give good results.
Keywords: Copper(II); Glycine; Biomacromolecular interactions; Radical scavenging activity